Original articleThe coexistence of pleomorphic xanthoastrocytoma and arteriovenous malformation. A case report - Nagańska, Ewa; Matyja, Ewa; Pucko, Emanuela; Ząbek, Mirosław (Folia Neuropathologica, 2013)
Pleomorphic xanthoastrocytoma (PXA) is a rare, low-grade astrocytic tumour corresponding to WHO grade II that is usually diagnosed in adolescents and young adults with epileptic seizures. Pleomorphic xanthoastrocytoma typically appears as a superficial, often cystic mass lesion predominantly affecting the temporal lobe. Cases with typical pathology and total tumour excision have a favourable prognosis. Occasionally, the tumour reveals anaplastic features and behaves more aggressively due to local recurrences or subarachnoid spread. The treatment of PXA includes gross total resection followed by neuroradiological monitoring. The association between vascular malformations and cerebral gliomas is rarely encountered, especially if both such lesions occur as separate parts of the same tumour. The vascular pathology of such changes most often refers to arteriovenous malformation (AVM), less frequently – cavernous angioma. The coexistence of PXA and AVM is extremely rare, especially when dealing with two distinct patterns found within the same tumour mass. We present a 36-year-old woman with tumour of parasagittal localization in the right occipital lobe that was composed of two different and clearly demarcated components: PXA and vascular lesion of AVM morphology. The pathogenesis of such coexistence remains still unclear.